Amazing Kitchen Tools - mamawag, eddie (International Journal of Arts, Sciences and Education, 2022)
Technology and Livelihood Education (TLE) is one of the nomenclatures in the implementation of the K to 12 Basic Education Program (BEP) and one of the components of this subject is Home Economics– Commercial Cooking. San Jose National High School is offering four (4) specializations in grade 7 and grade 8 as an exploratory subject; among of these specializations is Commercial Cooking. However, based from the result of the First Quarterly Assessment in Grade 7 TLE Commercial Cooking, 88% emerged as unmastered competencies. The competencies are divided into three (3); groups; First Priority (Needs Planned Intervention), Second Priority (Needs Immediate Remediation) and Third Priority (Needs Further Teaching). Among the least mastered competencies is Utilizing Kitchen Tools and Utensils. It is identified as the first priority (62%) that needs planned intervention. Hence, the proponent come up with this Strategic Intervention Materials entitled “ Amazing Kitchen Tools!!” to help the learners gain mastery of the competency.